Current trends and prospects in the development of pharmaceutical compositions with prolonged action based on poly(lactide-co-glicolide): a literature review - Lyzhniuk, Viktoriia; Udovytskyi, Vladyslav (Annals of Mechnikov’s Institute, 2026)
The development of prolonged-action drugs is a relevant and promising area of modern pharmaceutical science and practice. One of the best polymer carriers for creating prolonged-release dosage forms is considered to be poly(lactide-co-glycolide) (PLGA), due to its biocompatibility, biodegradability, and controllable physicochemical properties. The aim of the work is to systematically analyze the scientific literature on the use of poly (polylactide-co-glycolide) in the development of prolonged-action pharmaceutical compositions, including the characterization of the physicochemical properties of the polymer, research on the range of drugs based on it, a review of methods for their production, and the identification of promising areas for further scientific research. The research methodology was based on a comprehensive analytical review of scientific papers published in journals indexed in the international scientometric databases Scopus and Web of Science, as well as those presented in the specialized PubMed database. The work uses methods of critical analysis, information structuring, comparative data evaluation, and generalization of results. This work presents an analytical literature review on the use of PLGA polymer carriers for the development of pharmaceutical compositions with controlled and prolonged release of active pharmaceutical ingredients (APIs). The methods of synthesis and physicochemical properties of PLGA are characterized, and the key factors affecting polymer degradation are identified. A comprehensive analysis of the pharmaceutical market for PLGA-based drugs is performed. Various types of PLGA-based injectable pharmaceutical compositions are characterized, namely systems based on polymer microspheres and gels that form an in situ implant after subcutaneous administration, including an analysis of the mechanisms of API release from these forms. Modern promising methods for obtaining PLGA microspheres with prolonged API release are described, in particular emulsification, coacervation, spray drying, supercritical fluids, and microfluidic technologies. The properties of gels that form in situ implants are characterized, including phase inversion mechanisms and factors affecting the kinetics of API release. The main difficulties in the development of PLGA-based pharmaceutical compositions are identified, in particular, the problem of initial rapid API release, the lack of standardized methods for assessing the kinetics of active substance release, and the influence of polymer property variability on the reproducibility of the characteristics of finished dosage forms. The results of the study emphasize the effectiveness of using PLGA as a polymer carrier for the creation of highly effective prolonged-action drugs used to treat a wide range of diseases. The key tasks for future scientific research are to develop and validate standardized methods for studying the kinetics of active substance release, and to evaluate the effectiveness of PLGA systems using correlations between in vitro and in vivo studies. In addition, the creation of unified approaches to quality control of production processes remains a relevant area of focus in order to ensure the reproducibility and stability of innovative pharmaceutical compositions based on PLGA.